Starting from the future by looking to the past: reclaiming radical pedagogies, charting cartographies of imagination - Nivethitha Ram Ganapathiram; Andy Guise (Frontiers in Medicine, 2026)
This perspective piece offers a theoretical and pedagogical framework for delivering meaningful social justice education in medical curricula, grounded in the design of an anti-discrimination pilot programme for undergraduate medical students. Drawing on John Dewey, Paulo Freire, and bell hooks, we examine three contemporary challenges—neoliberal pedagogies, technological determinism, and manufactured scarcity—and propose three entangled responses: relational community-building, conscientização, and vulnerability. Playing with the linearity of time, itself a colonial logic, we reach back to enduring knowledge in tandem with working backwards from imagined futures, drawing our cartography of imagination.